2008
DOI: 10.1021/ac8005268
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Approach To Detect Apoptosis

Abstract: This paper reports an electrochemical approach for detection of apoptosis. Here we prepare a gold electrode modified with a helix peptide ferrocene (Fc)-GDGDEVDGC. Fc is used as an electroactive reporter and the peptide as a recognition and cleavage site of caspase-3, which is a special proteinase to apoptosis. Results show that this method may sensitively and specifically detect apoptotic cells with signal decline of 85%. This approach is different from the previous methods for apoptosis detection, because it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 21 publications
0
57
2
Order By: Relevance
“…A change of 120 millidegrees represents a surface change of approximately 1 ng mm −2 as described in previous reports [27][28][29]. To obtain well aligned aptamer monolayers [30], 1 mM MCH was injected into two channels for 1 h. As shown in Fig. 4, an increase in the SPR angle was observed, the adsorption of aptamer on SPR gold chip results in a big angle shift of 789 millidegrees.…”
Section: Immobilization Of Apt1 On Gold Chip Surfacementioning
confidence: 63%
“…A change of 120 millidegrees represents a surface change of approximately 1 ng mm −2 as described in previous reports [27][28][29]. To obtain well aligned aptamer monolayers [30], 1 mM MCH was injected into two channels for 1 h. As shown in Fig. 4, an increase in the SPR angle was observed, the adsorption of aptamer on SPR gold chip results in a big angle shift of 789 millidegrees.…”
Section: Immobilization Of Apt1 On Gold Chip Surfacementioning
confidence: 63%
“…Monolayer-modified electrodes have been developed for monitoring the action and activity of wide-ranging and relevant enzymes: matrix metalloproteinases, which are often overexpressed in diseases such as cancer (Fig. 11) [87]; serine proteases, involved in the tightly coordinated coagulation cascade [88,89]; cysteine proteases [90] such as caspase 3, related to cellular apoptosis [91]; HIV-1 protease [92]; integrating metal nanoparticles with carbon nanotubes on a gold electrode [93].…”
Section: Enzyme Substrates and Inhibitorsmentioning
confidence: 99%
“…Several detection methods have taken advantage of this activity and used this tetra-peptide motif to identify caspase-3. Xiao et al [23] have reported the use of a ferrocene-labelled DEVD peptide as an electrochemical reporter for caspase-3 activity. In the absence of caspase-3, a ferrocene oxidation signal was observed.…”
Section: Introductionmentioning
confidence: 99%